Organizational Justice, Trust And Organizational Commitment – A Comparison Between Permanent And Contingent Workers - S. MANIAM, GANESH (2004)
This study aims to examine the influence of organizational justice and trust towards organizational commitment, with job status as a moderator. This study is important due to the growing number of contingent workers being currently employed in many organizations. Many organizations are faced with the question if there are any difference in the commitment level of the permanent employees in comparison with contingent workers.